Improving access to epilepsy care for homeless patients in the Dublin Inner City: a collaborative quality improvement project joining hospital and community care. Issue 2 (29th April 2021) - Doran, Elisabeth; Barron, Enda; Healy, Laura; O'Connor, Lorraine; Synnott, Cara; Ní Cheallaigh, Clíona; Doherty, Colin
Abstract : Homelessness is associated with significant psychosocial and health disparities. The rate of epilepsy among this cohort is eight times greater than that in the settled population, and the associated morbidity is higher due to lack of integrated care, difficulties with treatment adherence, substance abuse and poor social circumstances. There is a high rate of seizure-related death in homeless patients. Seizures are one of the most common neurological cause for emergency department presentation among this population. The aim of this quality improvement project was to use a multistakeholder co-production approach to design a new pathway of care for homeless patients with epilepsy to improve access to specialist epilepsy care and to strengthen the links between hospital and community teams who manage this population. After several years of observation, stakeholder engagement and numerous tests of change, we have created a new care pathway and developed bespoke tools for primary care providers and for physicians working in the emergency department to enable them to assess and manage patients as they present, as well as provide access to remote epilepsy specialist support.